Experiences of individuals with intellectual disability who lecture in higher education - Mevold, Silje; Johansen, Leif Inge; Wynn, Rolf; Ramsdal, Gro H. (Frontiers in Psychiatry, 2023)
Prior studies have suggested that adults with intellectual disabilities who are in employment in general report a high level of well-being and life satisfaction. Less is known about which experiences and outcomes that are most important for the experiences of those who are employed.We interviewed six persons with intellectual disabilities that worked as lecturers at a health and social education programme at a university about which experiences and outcomes that they believed were of importance to their work experiences.The participants spontaneously focused on three main themes that described their experiences with work: the high degree of autonomy at work, their involvement in positive new relationships, and their experiences of accomplishment and coping on new social arenas.Although there were challenges, these were often overcome by working closely with another teacher.The three main themes by which the participants described their work experiences and outcomes can be related to the concepts of autonomy, relatedness, and competence. The experiences described by the participants are valuable for the future facilitation of work assignments for people with intellectual disability in ordinary working life.